Understanding clinical research - Lopes, Renato D.; Harrington, Robert A. (McGraw-Hill Medical, 2013)
Complete how-to guidance on conducting clinical research, this book addresses the operational challenges of clinical trials and provides a clear explanation of the methodologies necessary to interpret results. The book addresses all aspects of clinical trials, from design and implementation to statistics to regulatory scrutiny. A resource for students, residents, and clinicians who need a working knowledge of clinical research principles. The chapter authors are all leaders in the field and engaged in cutting edge clinical research. Use as a textbook, as a reference, and as a course guide for mandated clinical research training courses.